Climate change mitigation: learning from the past to unlock the hydropower potential of the Derbyshire Derwent catchment - Jackson, Ian (2025)
For Derbyshire communities seeking climate change mitigation opportunities, the hydropower (HEP) potential of the historic water-powered textile mills of the Derwent Valley Mills World Heritage Site (DVMWHS) is an obvious starting point. Waterpower is a core story of the DVMWHS, in the heart of the Derbyshire Derwent catchment (DDC), but there is limited understanding of how the early industrial watermill owners overcame the natural and man-made challenges they faced, many similar to those faced today. This research aims to improve our understanding of the harnessing, management and use of waterpower, particularly during the Georgian period, to identify what lessons we can learn to repower the remaining HEP opportunities on revitalised DDC waterways, supporting our climate change mitigation efforts. DDC waterpower sites, by waterway, were identified using historic OS maps and a gazetteer produced. Individual watermill timelines were produced, capturing each mill’s use, power and water management development. The gazetteer included historic mills, non-mills (e.g. Chatsworth House) and man-made water sources for power (e.g. lead mine drainage soughs). External factors were also considered, capturing the wider impacts of political, economic and legislative changes on ‘milling power’ over time. Historically, government support has been critical for waterpower, with parliament repeatedly listening to the industrial watermill owners, protecting their milling power, including in the Salmon Fishery Act (1861). However, run-of-river (small) HEP collapsed in the 1950s-70s, with the government focussed on building the fossil-fuelled electricity grid, and the newly formed water authorities charging the mills for ‘borrowing’ water for power. From the 1990s, the climate change driven need for renewable energy saw a mini revival in small HEP, but the ending of government subsides supporting small, local, renewable energy in 2019, paused this. This research uncovered the millowners’ wider influence on river stewardship, using the mills’ weirs, floodgates and sluices to control the waterways, including flood management, maintaining fisheries and river morphology, issues critical to HEP development today. Following the closure of run-of-river HEP from the 1950s, many weirs, floodgates and sluices were no longer used or maintained, and today are viewed as redundant barriers by river ecologists. Much of this infrastructure remains, providing historic watermill sites with an opportunity to be repurposed as green power stations, and to play a role in current river stewardship challenges, as they did in the past.